Shandong’s Yintan Town and China’s “Ghost City” Phenomenon - Wang, Qianyi; Li, Ran; Cheong, Kee Cheok (MDPI, 2019)
Although much research has been devoted to urbanization and city growth, urban dynamics also include city decay and renewal. Extant theories and models have been developed to explain these dynamics. They do not, however, fit the experience of China's "ghost cities". These cities have been characterized as state-built but minimally inhabited, testimony to planning failure by the monolithic Chinese state. The goal of the article is to provide in-depth insights to China's ghost city phenomenon and its effects to residents from local stakeholders' perspectives. A review of Shandong's new Yintan city reveals many ghost city attributes, but its development trajectory was at odds with this stereotype. Yintan's lack of success was attributable to too little, not too much, state intervention, reflecting limited state capacity to develop and manage the new city by Rushan, the nearby small city seeking to capitalize on the central government's development imperatives. These distinctive features notwithstanding, generic key drivers of city growth can help explain Yintan's lack of development, in a sense, reconciling the city's experience with extant research elsewhere. © 2019 by the authors.